Using photographs in social and historical research - Tinkler, Penny (SAGE, 2013)
Written by one of the world's leading authorities on image-based methods this is the first book to investigate, in depth, the use of photographs and photo images in research. Using real world case studies and over 40 images it explains the conceptual and methodological approaches needed to study photographs and images.